Callochiton monteleonensis n. sp., First record of polyplacophora (Mollusca) from the Neogene of Argentina - Urteaga, Diego Gaston (2011)
A new species of chiton is described from early Miocene deposits of the Monte Len Formation, in Santa Cruz Province, Argentina. Callochiton monteleonensis n. sp. clearly differs from known fossil and Recent species of the southwestern Atlantic because the central area of its intermediate valves has a stepped appearance, in which each step is marked by a longitudinal rib. It is similar to Callochiton kapitiensis Mestayer, 1926, a Recent species from New Zealand. Biogeographic implications are discussed. This is the first record of a polyplacophoran from Neogene deposits of Argentina.